PENGARUH CORPORATE GOVERNANCE TERHADAP ISLAMIC SOCIAL REPORTING (ISR) DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERATING (Studi Kasus pada Perusahaan Asuransi Syariah di Indonesia Tahun 2016-2021) - Ulya, Hakimatul; Khabib, Nur (Jurnal Akuntansi Syariah (JAkSya), 2023)
This study aims to determine the effect of corporate governance on Islamic social reporting (ISR) with firm size as a moderating variable in Islamic insurance companies. The problem in this study is the low disclosure of Islamic social reporting in companies. The type of research used in this research is secondary research with a quantitative approach. The sampling technique uses the SPurposive technique with a total sample of 10. The data collection technique uses year-end reports. The data analysis technique used to answer the research hypothesis is a statistical test. The results of this study indicate that: (1) DPS has a positive and not significant effect on ISR (2) Tax knowledge has a positive and significant effect on individual taxpayer compliance at the Regional Military Command Leverage variable has a positive and significant effect on ISR (3) probability variable has a positive and significant effect on ISR. not significant on ISR. (4) DPS which is moderated by firm size has a negative and insignificant effect on ISR. (5) Leverage moderated by firm size has a negative and significant effect on ISR (6) Profitability moderated by firm size has a negative and insignificant effect on ISR. Keywords: Sharia Supervisory Board, Leverage, Profitability, Islamic Social Reporting